A3.20 The calcium sensor stromal interaction molecule 1 (STIM1) controls regulatory B cell functions and its activity is impaired in Systemic Lupus Erythematosus patients. (31st January 2014) - Fali, T; Renaudineau, Y; Burgos, M; Bariller, E; Jousse, S; Saraux, A; Hanrotel, C; Cornec, D; Jamin, C; Mignen, O; Pers, J O
Abstract : Background and Objectives: The immunosuppressive function of regulatory B cells (Breg) is defective in B cells from systemic lupus erythematosus (SLE) patients. Since the Ca 2+ pathway is also altered in SLE B cells, the aim of the study was to explore the contribution of the Ca 2+ channel Orai1 and its regulator, the stromal interaction molecule 1 (STIM1), on regulatory B cell functions. Materials and Methods: Thirty SLE patients and healthy controls (HC) were included in the study. Orai1 and STIM1 expressions were explored in CD40/CpG activated B cells, and in the stimulated (anti-CD3, anti-CD28 plus CpG-ODN 2006) T- and B- cell autologous co-culture Breg model. Transfection were used using either siRNAs to down-modulate STIM1 in SLE B cells, or either the cDNA STIM1 vector in HC B cells. Results: After 3 days, in CD40/CpG activated HC B cells, and in HC B cells stimulated during co-cultures, acquisition of the Breg phenotype (IgD/CD38/CD24/CD5 high ) was associated with an over-expression of the Ca 2+ regulator STIM1 (x10.8 and x7.1 fold increase respectively). At day 4 and even more at day 5, STIM1 expression declined in co-cultures and this down-regulation was accompanied with IL-10 and TGF-beta up-regulation in B cells, FoxP3 + regulatory T cell expansion, and a reduction of T cell proliferation. Expression of the Ca 2+ channel Orai1 was stable. In SLE B cells, STIM1 expression was overexpressed at basal level when compared to HC B cells (x4.3 fold) and remains elevated in B cells during all the time of the autologous co-culture (x8.8 fold). Then we hypothesised that maintaining high levels of STIM1 was critic in the regulatory capacity of SLE B cells. Accordingly, we demonstrated that STIM1 downregulation in SLE B cells, using a specific siRNA, was effective to restore IL-10, but not TGF-beta, expression, FoxP3 + regulatory SLE T cell expansion, and SLE T cell inhibition. In HC B cells, forcing STIM1 expression, with a STIM1 vector, was effective to reproduce the abnormalities observed in SLE B cells. No association was observed between STIM1 expression at basal level and organ involvement, disease activity (SLEDAI), or serological parameters thus suggesting that STIM1 over-expression and Ca 2+ dysregulations are primary events in SLE. Conclusions: Altogether, this study reveals that acquisition of the Breg phenotype and Breg functions are tightly regulated by STIM1. Furthermore, this observation could provide innovative B-cell based treatment to convert B cells into immunosuppressive cells with applications in human autoimmunity and in SLE. Key words: lupus, regulatory B cells, calcium, STIM1, IL-10